Impact of sequelae of visceral leishmaniasis and their contribution to ongoing transmission of Leishmania donovani. Issue 6 (7th October 2019) - Duthie, Malcolm S; Goto, Yasuyuki; Ghosh, Prakash; Mondal, Dinesh
ABSTRACT: Visceral leishmaniasis (VL) in the Old World is caused by infection with Leishmania donovani . Although the numbers of new reported cases of VL in Africa have been relatively stable for several years, the low numbers currently reported on the Indian subcontinent suggest a positive impact of new treatments and intervention strategies. In both regions, however, VL relapse and post-kala-azar dermal leishmaniasis (PKDL) maintain infectious reservoirs and therefore present a threat to control programs. In this review, we outline the evolving appreciation of PKDL as an impactful disease in its own right and discuss the various diagnostic methods that can be applied for the detection and characterization of PKDL cases. We also highlight the data that indicate the potential, and likely contribution, of PKDL cases to ongoing transmission of L. donovani . Abstract : A minireview article emphasizing the importance of the post kala-azar dermal leishmaniasis sequelae to visceral leishmaniasis, with particular attention given to the social and diagnostic limitations that are currently experienced, along with the tools that are emerging that could change the situation for the better.